Posisi Kepala dan Tubuh sebagai Salah Satu Penyebab Keluhan Nyeri Kepala - Gimawati Muljono (Faculty of Dentistry, Universitas Indonesia, 2015)
Headache is a disturbance of multifactorial causes. After many researches and debates, dental profession had accepted occlusion factors and temporomandibular disorders as a cause of headache. Unfortunately, since head and body posture have not been realized as a cause of headache, this posture condition is often neglected by patients, physicians, and dentists. Many cases with headache symptom could resemble any headache caused by any disturbances within skull itself, in the eyes, or ears. Radiographic observation of head posture could be a part of examination process to establish diagnosis and to identify the cause of headache symptoms. The ability to differentiate diagnosis between normal anatomic structures with abnormal, and pathological conditions is useful to eliminate possibilities of any diseases with headache as one of the manifestation, for instance: infections and malignancy. From 3 cases described in this study, it is obviously important that relationship between head and body posture as the possible cause of headache should be identified through radiographic invvestigation, before doing any treatment.